Colored amazons: crime, violence, and black women in the City of Brotherly Love, 1880-1910 - Gross, Kali N. (Politics, history, and culture, 2006)
Notes from the author : crime and Black women's history -- Of law and virtue : Black women in slavery, freedom, and early criminal justice -- Service savors of slavery : labor, autonomy, and turn-of-the-century urban crime -- Tricking the tricks : violence and vice among Black female criminals -- Roughneck women, pale representations, and dark crimes : Black female criminals and popular culture -- Deviant by design : race, degeneracy, and the science of penology -- Conclusion: "She was born in this prison" : Black female crime, past and present